Perceptions of plagiarism by future teachers: ethical and pedagogical dimensions - Jeffrey, Denis; Dias, Wagner (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
This article presents the data of a study on plagiarism conducted in 2018 among a population of 300 final year students enrolled in a teacher education program at Laval University. Its primary purpose was to draw a portrait of the perceptions of future teachers of plagiarism among elementary and secondary students. The questionnaire included 22 questions related to their experiences of plagiarism and pedagogical interventions to deal with it. Three questions led this research: do future teachers 1) have sufficient knowledge of plagiarism? 2) Do they know the pedagogical and ethical actions to deal with plagiarism upstream and downstream? 3) Are they well trained on plagiarism issues? Although future teachers report having a good knowledge of plagiarism, they confess having gaps in each of the three research questions. We conclude that future teachers should be better trained to handle plagiarism in all its forms upstream and downstream. Keywords: plagiarism, teacher training, school research, ethics